2013
DOI: 10.3945/ajcn.113.058388
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear transcription factor κ B activation and protein turnover adaptations in skeletal muscle of patients with progressive stages of lung cancer cachexia

Abstract: In lung cancer, muscular NF-κB activity is induced by factors contained within the circulation. Autophagy may contribute to increased muscle proteolysis in lung cancer cachexia, whereas the absence of downstream changes in phosphosubstrates despite increased Akt phosphorylation suggests impaired anabolic signaling that may require targeted nutritional intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
143
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(153 citation statements)
references
References 51 publications
8
143
2
Order By: Relevance
“…40 In centronuclear myopathy, a naturally occurring mutation leading to inactivation of MTMR14/hJumpy (myotubularin-related protein 14) activates autophagy, suggesting that aggravated autophagy is important in the etiology of centronuclear myopathy. 41 Excessive autophagy contributing to muscle wasting has also been shown in tumor-bearing animals, 42 in a systemic burn injury model in mice, 43 in patients with progressive stages of lung cancer cachexia, 44 and in chronic obstructive pulmonary disease patients. 45 These studies suggest that aggravated/excessive autophagy is responsible for the loss of muscle mass, whereas defective autophagy leads to the degeneration of muscle fiber, severe reduction in muscle strength, and metabolic disorders.…”
Section: Basic Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 In centronuclear myopathy, a naturally occurring mutation leading to inactivation of MTMR14/hJumpy (myotubularin-related protein 14) activates autophagy, suggesting that aggravated autophagy is important in the etiology of centronuclear myopathy. 41 Excessive autophagy contributing to muscle wasting has also been shown in tumor-bearing animals, 42 in a systemic burn injury model in mice, 43 in patients with progressive stages of lung cancer cachexia, 44 and in chronic obstructive pulmonary disease patients. 45 These studies suggest that aggravated/excessive autophagy is responsible for the loss of muscle mass, whereas defective autophagy leads to the degeneration of muscle fiber, severe reduction in muscle strength, and metabolic disorders.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…In patients with lung cancer cachexia, enhanced autophagy has been shown to increase muscle proteolysis, suggesting that impaired or exaggerated autophagy in the muscle tissue plays a role in the etiology of pathological conditions and is responsible for the damage of the muscle tissue. 42,44 The immediate post-exercise phase is characterized by increases in catabolic signals such as IL6/interleukin 6 and protein turnover. In healthy, active human subjects, infusion of recombinant IL6 causes a significant increase in the net release of amino acids from the muscle.…”
Section: Exercise As a Modelmentioning
confidence: 99%
“…NF‐κB activity is increased in COPD patients compared with controls38, 39 and in cachectic COPD patients compared with non‐cachectic COPD patients 38, 40. Furthermore, limb muscle NF‐κB activity is increased in patients with lung cancer cachexia 41. FOXO mRNA and protein expression are increased in patients with COPD,38, 39, 42, 43, 44, 45 seemingly independent of body composition, although it is noticeable that in all studies, the patient group showed signs of emphysema.…”
Section: New Insights In the Pathophysiology Of Muscle Wasting In Chrmentioning
confidence: 94%
“…Together, these studies show an increase in protein synthesis signalling in the limb muscles of cachectic COPD patients compared with non‐cachectic COPD patients, but no alteration in the general COPD population. In patients with lung cancer‐related cachexia, AKT activation is increased without concurrent activation of MTOR or its downstream targets 41. This may indicate that, although impaired AKT signalling is found in lung cancer cachexia, AKT signalling is largely intact in COPD‐induced muscle wasting.…”
Section: New Insights In the Pathophysiology Of Muscle Wasting In Chrmentioning
confidence: 99%
See 1 more Smart Citation